Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species - Barros, Luana Machado; Soares, Matheus Mickael Mota; de Freitas-Silva, Rafael Augusto Pinheiro; Ale-Rocha, Rosaly (Zootaxa, 2019)
Three new species of Chvalaea Papp & Földvári are described and illustrated: Chvalaea annularis sp. nov., C. ecuadoriensis sp. nov., and Chvalaea sinclairi sp. nov. In addition, an illustrated key, distribution map, new records, and updated diagnoses of all Neotropical species are presented.